Unpacking the African Backlash to the International Criminal Court (ICC): The Case of Uganda and Kenya (Strathmore Law Journal, 2020)
From early bright beginnings and close cooperation, African relations with the International Criminal Court (ICC or Court) have recently witnessed a sharp deterioration. The explanations for this fall-out vary from the personal style of the first Prosecutor of the Court—Luis Moreno Ocampo—to the lack of a comprehensive appreciation of the reasons for which the institution was established in the first instance. This article specifically zeroes in on the troubled interactions between the Court and the governments of Uganda and Kenya. These two instances demonstrate that while the charge of anti-African bias has become the dominant discourse of contemporary scholarship on the issue, structural and systemic factors are not given enough attention. Particular attention is given to the way the cases of the Lord’s Resistance Army (LRA) and President Uhuru Kenyatta (from Uganda and Kenya respectively) found their way to the ICC and the subsequent developments relating thereto. In doing so, the article explores, among other factors, the way International Criminal Justice was politicised, and its links to enduring questions of global political and economic inequality. Such conditions of inequality find manifestation in the backlash by African countries towards what has been described as the ICC’s selective approach. At the same time, opportunism and double-standards abound on all sides as there is both an inconsistent and hypocritical embrace of the basic tenets of International Criminal Law and Justice. Ultimately, the victims of human rights violations are short-changed while those actors who really need to be brought to account remain beyond sanction.